(NtEKTONIKA PLITY kARTOGRAFOW (B((NtIHIJ OKEAN(B) /s - (NaNOSOW(B, (Ng(B.(Ni(B.s; (NkAROGODINA(B, (Ni(B.(Np(B.s; (NsY^EW(B, (NpAWEL mAKSIMOWI^s ((NmOSKWA (B:s (NnAUKA(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 83-87s
Keywords: (NpLITA kARTOGRAFOWs -- (NtIHIJ OKEANs; (NtEKTONIKAs -- (NtIHIJ OKEANs